The Technical Essence of Poda Na Lima as the Foundation of Public Health Philosophy - Iskandarsyah Siregar (Britain International for Academic Research (BIAR-Publisher), 2023)
The latest technology considered relevant to the times' needs makes people from the newest civilisation abandon and forget traditional technology that has even been tested for hundreds of years in overcoming various problems of its time. One is Poda Na Lima, philosophical teaching about mental attitude and lifestyle in Batak civilisation. Now, this philosophy is still known in the Batak community. However, the problem is in the implementation. This study explores and translates the values of Poda Na Lima to draw their relevance to the potential for solving the Covid-19 problem, which is still a problem in the global community. This research and study analyse the Poda Na Lima, a philosophy using the Sociosemiotics analysis knife. The sociosemiotics point of view is appropriate in describing the problems related to this research and study. It becomes a research method, analysis, and conclusion that can ultimately prove that the values and derivatives of the implementation of Poda Na Lima can be used as standards and guidelines for overcoming the Covid-19 problem and any other public health problems.